Fairness as a Program Property - Albarghouthi, Aws; D'Antoni, Loris; Drews, Samuel; Nori, Aditya (Fairness, Accountability, and Transparency in Machine Learning (FATML), 2016)
We explore the following question: Is a decision-making program fair, for some useful definition of fairness? First, we describe how several algorithmic fairness questions can be phrased as program verification problems. Second, we discuss an automated verification technique for proving or disproving fairness of decision-making programs with respect to a model of the population.